Computational proofs of congruences for 2-colored Frobenius partitions - Dennis Eichhorn; James A. Sellers (International Journal of Mathematics and Mathematical Sciences)
In 1994, the following infinite family of congruences was conjectured for the partition function cΦ2(n) which counts the number of 2-colored Frobenius partitions of n: for all n≥0 and α≥1, cΦ2(5αn+λα)≡0(mod5α), where λα is the least positive reciprocal of 12 modulo 5α. In this paper, the first four cases of this family are proved.